2006
DOI: 10.1007/s00264-006-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental versus computer-assisted total knee replacement for medial compartment knee arthritis: a matched paired study

Abstract: Patients older than 60 with unicompartmental knee arthritis can be treated with total or unicompartmental knee replacement. The aim of this study was to compare the results of matched paired groups of patients with isolated medial compartment knee arthritis replaced with either UKR (group A) or computer-assisted TKR (group B). The results included 68 knees at a minimum follow-up of 3 years. All patients had a varus deformity no greater than 8º and a BMI lower than 30. Patients were matched in terms of preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 28 publications
(28 reference statements)
1
42
0
Order By: Relevance
“…There have been reports with larger numbers of conversions to total knee replacements requiring metal wedges and allografts [9,25] in the presence of loosening and osteolysis. The functional results of unicompartmental knees converted to total knee replacements have been found to be worse than primary knee replacements [9], but the improved kinematics and consistently better knee scores [15,20,28] in successful medial unicompartmental knee replacements justify their use over total knee replacements in appropriate patients.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports with larger numbers of conversions to total knee replacements requiring metal wedges and allografts [9,25] in the presence of loosening and osteolysis. The functional results of unicompartmental knees converted to total knee replacements have been found to be worse than primary knee replacements [9], but the improved kinematics and consistently better knee scores [15,20,28] in successful medial unicompartmental knee replacements justify their use over total knee replacements in appropriate patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have confirmed this theory [1,3,9,24,39], others have shown that there is no difference in orientation or alignment of the femoral or tibial components than that achieved by conventional methods [12,22,23,42]. When evaluating the published reports on navigation knee arthroplasty, two important factors limit comparisons among clinical series.…”
Section: Alignmentmentioning
confidence: 99%
“…Medial unicondylar knee arthroplasty (UKA) is an increasingly popular method of knee replacement in patients with isolated anteromedial osteoarthritis (OA) of the knee with very good long-term results [1][2][3]. It is recommended that UKA should be done if there is full thickness cartilage loss (FTCL) with ''bone on bone'' visible on the preoperative radiograph [4].…”
Section: Introductionmentioning
confidence: 99%